Fibroblast growth factor 21 alleviates acute pancreatitis via activation of the Sirt1‐autophagy signalling pathway. Issue 9 (31st March 2020) - Chen, Qiongzhen; Li, Jinmeng; Ma, Junfeng; Yang, Xiaoning; Ni, Ming; Zhang, Yali; Li, Xiaokun; Lin, Zhuofeng; Gong, Fanghua
Abstract: Fibroblast growth factor 21 (FGF21), a metabolic hormone with pleiotropic effects on glucose and lipid metabolism and insulin sensitivity, alleviates the process of acute pancreatitis (AP). However, its mechanism remains elusive. The pathological and physiological characteristics of FGF21 are observed in both patients with AP and cerulein‐induced AP models, and the mechanisms of FGF21 in response to AP are investigated by evaluating the impact of autophagy in FGF21‐treated mice and cultured pancreatic cells. Circulating levels of FGF21 significantly increase in both AP patients and cerulein‐induced AP mice, which is accompanied by the change of pathology in pancreatic injury. Replenishment of FGF21 distinctly reverses cerulein‐induced pancreatic injury and improves cerulein‐induced autophagy damage in vivo and in vitro. Mechanically, FGF21 acts on pancreatic acinar cells to up‐regulate Sirtuin‐1 (Sirt1) expression, which in turn repairs impaired autophagy and removes damaged organs. In addition, blockage of Sirt1 accelerates cerulein‐induced pancreatic injury and weakens the regulative effect in FGF21‐activated autophagy in mice. These results showed that FGF21 protects against cerulein‐induced AP by activation of Sirtuin‐1‐autophagy axis.